2011
DOI: 10.2307/23044048
|View full text |Cite
|
Sign up to set email alerts
|

What Signal Are You Sending? How Website Quality Influences Perceptions of Product Quality and Purchase Intentions

Abstract: An electronic commerce marketing channel is fully mediated by information technology, stripping away much of a product's physical informational cues, and creating information asymmetries (i.e., limited information). These asymmetries may impede consumers' ability to effectively assess certain types of products, thus creating challenges for online sellers. Signaling theory provides a framework for understanding how extrinsic cuessignals-can be used by sellers to convey product quality information to consumers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
529
4
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(567 citation statements)
references
References 86 publications
17
529
4
17
Order By: Relevance
“…Everard and Galletta (2005) found the intent to purchase from a website depended on trust in the website, and they reason that trust reflects the website's credibility. Wells et al (2011) found that signals about the credibility of a website moderated the effect of website quality on product quality such that the quality of a website had a stronger effect on product quality if an individual saw the website as credible. In turn, they found that product quality affected purchase intentions.…”
Section: Website Credibility and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Everard and Galletta (2005) found the intent to purchase from a website depended on trust in the website, and they reason that trust reflects the website's credibility. Wells et al (2011) found that signals about the credibility of a website moderated the effect of website quality on product quality such that the quality of a website had a stronger effect on product quality if an individual saw the website as credible. In turn, they found that product quality affected purchase intentions.…”
Section: Website Credibility and Qualitymentioning
confidence: 99%
“…For example, Everard and Galletta (2005) found that website quality was related to trust in the website, which was, in turn, related to the intent to purchase from the website. Wells, Valacich, and Hess (2011) report that perceived credibility moderated the effect of website quality on product quality. One can investigate issues related to website quality and credibility from several different theoretical perspectives.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To achieve this, organizations focus on building a visually appealing website and attempt to reduce errors in information accuracy and website navigation. Additionally, extant research has suggested that brand image of an organization and its order management processes can positively influence consumer perceptions [21]. Based on such factors, it seemed necessary to perform research on the effects of four important organizational effort components: the visual appearance of a web-site, its order fulfillment process, its absence of errors, and its brand image.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian terdahulu mengenai penggunaan situs web untuk keperluan komersial (Wells, Valacich, dan Hess 2011) dan untuk keperluan pengembangan penelitian sistem informasi (Loiacono et al 2007) menunjukkan bahwa kualitas situs web mempengaruhi tingkat kepercayaan pengguna situs web. Penelitian ini merupakan pengembangan penelitian Wells et al (2011) …”
unclassified